Complementary Reflectance and Carbon Dots Fluorescence Imaging Using Endoscopic Scanner - Leong Y.S.; Bakar M.H.A.; Mokhtar M.H.H.; Arsad N.; Zan M.S.D.; Bakar A.A.A. (Institute of Electrical and Electronics Engineers Inc., 2025)
Endoscopic imaging plays a crucial role in biomedical research, offering insights into biological structures and chemical processes. In this study, we present a fibre pair cantilever-based endoscopic scanner capable of employing confocal reflectance and carbon dots-based fluorescence imaging. Fluorescent microspheres were used to verify the fluorescence detection capability of the proposed scanner. Subsequently, a carbon dots-labelled sample was imaged and analysed. The results show that the confocal reflectance images capture the surface profile of the sample while the fluorescence images detect the emitted fluorescence signals. The findings show the complementary strength between confocal reflectance and carbon-dots based fluorescence modalities for precise localisation of fluorescence signals within the sample. The proposed endoscopic scanner shows the potential of multimodal endoscopic imaging for advancing biomedical research. ? 2024 IEEE.